2018
DOI: 10.1084/jem.20161714
|View full text |Cite
|
Sign up to set email alerts
|

GPR56/ADGRG1 regulates development and maintenance of peripheral myelin

Abstract: This study identifies GPR56/ADGRG1 as a conserved regulator of peripheral nervous system myelination and defines a novel interacting partner of GPR56: plectin. This study is directly relevant to human health because mutations in GPR56 and PLECTIN cause diseases with neuropathic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 68 publications
(160 reference statements)
0
58
0
Order By: Relevance
“…Mutations in the plectin gene are responsible for human diseases denominated plectinopathies [247]. Among these, the most common is epidermolysis bullosa simplex, with muscular dystrophy and neuropathy-like symptoms due to defects in the peripheral myelin ultrastructure [246,279].…”
Section: Mutations In Cytoskeletal Genes Associated With Neurodegenermentioning
confidence: 99%
“…Mutations in the plectin gene are responsible for human diseases denominated plectinopathies [247]. Among these, the most common is epidermolysis bullosa simplex, with muscular dystrophy and neuropathy-like symptoms due to defects in the peripheral myelin ultrastructure [246,279].…”
Section: Mutations In Cytoskeletal Genes Associated With Neurodegenermentioning
confidence: 99%
“…Hence, Gpr56 deficiency prompts the premature cell cycle exit of OPC, leading to less mature oligodendrocytes ( 23 , 31 ). In a more recent study, GPR56 was shown to be also involved in myelin development and maintenance in the peripheral nervous system by interacting with plectin ( 33 ).…”
Section: Biological and Cellular Functions Of Gpr56mentioning
confidence: 99%
“…These structural features make aGPCRs plausible transducers for cellular responses to ECM interactions, and specific aGPCRs have emerged as mechanical receptors and as transducers of cell-matrix interactions ( Scholz et al, 2015 ; Petersen et al, 2015 ; Langenhan et al, 2016 ). Prior work has defined functions for several aGPCRs in the development of myelinating glial cells in both the peripheral and central nervous systems ( Monk et al, 2009 ; Petersen et al, 2015 ; Ackerman et al, 2015 ; Giera et al, 2015 ; Langenhan et al, 2016 ; Shin et al, 2013 ; Ackerman et al, 2018 ). In particular, the aGPCR ADGRG1 (also known as GPR56) has been shown to regulate OL development and CNS myelination ( Ackerman et al, 2015 ; Giera et al, 2015 ; Salzman et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%